(untitled) (Anwer Khan Modern Medical College Journal, 2011)
Individual with type 2 diabetes is a high risk group for both adverse cardiac as well as renal events. GFR is an independent predictor of cardiovascular morbidity and mortality. Reduced GFR is associated with a high prevalence of cardiovascular risk factors and higher prevalence of cardiovascular disease. The study was designed to explore the association between reduced GFR and cardiovascular events in diabetic subjects. It was a case-control study. One hundred and twenty nine (129) male subjects with cardiac event or events were selected. Diabetes of them 50 was type 2 and 79 were non diabetic. Modification of diet in renal disease study equation (eGFR) to estimate GFR was used and examined the prevalence of cardiovascular events in both groups. Unpaired t-test and chi square test were done to find out the level of significance. eGFR was compared between the study groups and significant differences were observed (p value <0.01). Reduced GFR (by estimating MDRD equation) is associated with cardiac event or events and should perform as routine assessment of diabetic patients. Key word: MDRD (Modification of Diet in Renal Disease); eGFR (Estimated Glomerular Filtration Rate); Type 2 Diabetes DOI: 10.3329/akmmcj.v2i1.7464 Anwer Khan Modern Medical College Journal 2011; 2(1): 06-08